Codeswitching between English and French on an online discussion forum - Kirsimägi, Margus (My University, 2024)
This master’s thesis examines codeswitching between English and French on an online discussion forum. The purpose of the study is to examine in what contexts does codeswitching take place, what types of codeswitching occur in the discussion forum, and what are the functions of different codeswitches. The materials consisted of 582 forum posts that were analysed for French codeswitches. 150 posts in total contained codeswitching. The analysed codeswitches were divided into intersentential, intrasentential or metalinguistic commentary categories on the basis of the structure of codeswitches. Intrasentential switches are also categorised into nouns, adjectives, verbs etc. The codeswitches were also analysed in terms of their function in a context and divided into several different categories, such as cultural switches, language discussion, quotations, and humour. The results show that intrasentential codeswitching occurs much more frequently than intersentential switching. Intrasentential switches consisted of different French words or short French phrases. The functional analysis showed that cultural switches occur much more frequently than any other function category in the data. Cultural switches often referred to objects and concepts specific to French culture and society. Language discussion codeswitches were also quite frequent. These involved discussion about the French language, how to translate certain words into English or discussion about the meanings of different French words.
Keywords: Codeswitching, French, English, Computer-mediated communication